Molecular Genetics Informs Spatial Segregation of Two Desert Stream Gila Species. Issue 1 (2nd January 2017) - Marsh, Paul C.; Clarkson, Robert W.; Dowling, Thomas E.
Abstract: Headwater Chub Gila nigra and Roundtail Chub G. robusta are two distinct but morphologically similar cyprinid species that historically were parapatric in Fossil Creek (Gila River basin) in central Arizona. The creek was chemically treated in 2005 to eradicate nonnative fishes, and chubs salvaged before the treatment were repatriated afterward. Annual samples from multiple sites along a transect throughout the treated reach were characterized for mtDNA and microsatellites from 2008 to 2014. Genetic variation was compared within and among Fossil Creek samples and with reference material for Headwater Chub from Fossil Springs at the headwaters of the creek and for Roundtail Chub from the Verde River and West Clear Creek. Measures of mtDNA and microsatellite diversity identified significant differences among Headwater Chub from Fossil Springs, Roundtail Chub from the Verde River, and samples above and below Irving Falls, a natural fish barrier within the treatment reach. The frequency of Headwater Chub mtDNA was low at the most downstream sampling sites, progressively increasing upstream. There was also temporal variation, with Headwater Chub mtDNA generally becoming rarer in later samples. F -statistic analysis of microsatellite data and Bayesian clustering of microsatellite genotypes with STRUCTURE were generally consistent and identified three groups: Headwater Chub and two forms of Roundtail Chub. Using the species assignments provided by STRUCTURE and mitotypes, we found 153 "pure" Headwater Chub and only a single pure Roundtail Chub above Irving Falls and 27 pure Headwater Chub and 398 pure Roundtail Chub below the falls. Tests of cytonuclear disequilibrium indicated nonrandom mating (with the rare species more likely to mate than the more common one) and/or selection against hybrids. These data support the recognition of the Headwater Chub as a distinct full species and demonstrate that conservation actions within the genus Gila should typically be carried out at the population level. Received April 8, 2016; accepted August 16, 2016